Characterization of the IVS-II-821 (A>C) (HBB: c.316-30A>C) Mutation in a β-Thalassemia Phenotype in Iran. (2nd January 2019) - Azimi, Azam; Nejati, Parham; Tahmasebi, Soosan; Alimoradi, Sasan; Alibakhshi, Reza
Abstract: β-Thalassemia (β-thal) is the most frequently observed hereditary blood disorder that results from genetic defects causing deficient synthesis of hemoglobin (Hb) polypeptide chains. Detecting thalassemia mutations are necessary for prenatal diagnosis (PND) programs leading a better quality of life for the patients, as well as a reduction in the cost of their medical care. There are more than 900 different genomic mutations of the β-globin gene described in the human hemoglobin variant (HbVar) database. In this study, we identified a mid-intronic mutation at IVS-II-821 (A>C) ( HBB : c.316-30A>C) position in the HBB gene of an Iranian proband and two of her siblings that was associated with β-thal clinical features. Direct DNA sequence analysis was performed by mutation scanning of the β-globin gene. Based on the observed β-thal phenotype and bioinformatics analysis results, we concluded that this β-globin gene mutation was associated with a mild phenotype of β-thal through activating potential splice sites by creating exonic splicing enhancers (ESEs), exon-identity element (EIE) and exonic splicing regulatory sequences (ESRs) sites.